Multiple Sclerosis: Molecular Pathogenesis, Prevalence, and Major Risk Factors Contributing to Its Distribution in Benghazi City - ELghuol, Maati; Fatma ELmestiri; Sara Eljazwi; Zainab Aloraibi; Muna Bushiha; Retaj Alomami; Maram Alfargani; Sarah Salih (AlQalam Journal of Medical and Applied Sciences, 2026)
Multiple sclerosis (MS) is a chronic autoimmune disease affecting the central nervous system, primarily causing demyelination of neurons. It impacts around 2.8 million people globally, with higher prevalence in the USA and the Middle East and North Africa (MENA) region. MS is a multifaceted condition with an unclear causative origin, believed to arise from a combination of genetic, environmental, and lifestyle influences. Genetic factors play a crucial role in the susceptibility to MS; specific genes, such as TNFRSF1A and TNFSF13B, are associated with an elevated risk and integral to the pathogenesis of MS. Multiple sclerosis risk is also influenced by several environmental factors, including viral infections, smoking, and a deficiency in vitamin D. Highlighting the complex interplay of genetic and environmental influences that contribute to the etiology of MS disease. The study used a mixed-methods design to retrospectively analyze 128 patient records from the Benghazi Medical Centre (BMC) spanning 2021 to 2025, along with a literature review of the disease’s characteristics, molecular pathogenesis, and associations with viral infection. This study on multiple sclerosis (MS) in Benghazi indicated a low prevalence of the disease generally, with the majority of cases occurring in women aged 20 to 29, who represented 69% of those diagnosed. Over the course of the study, a gradual increase in cases was observed, starting with 28 recorded instances in the first year and rising to 49 by the final year, reflecting a slight increase in the number of diagnosed MS patients in recent years. Therefore, the present study emphasizes the urgent need for increased public awareness of the risk factors associated with MS, early detection, and the implementation of stronger diagnostic strategies, particularly for viral infections, as well as the establishment of region-specific prevention programs to manage MS effectively in Libya.